Peatland dynamics: A review of process-based models and approaches - Mozafari, Behzad; Bruen, Michael; Donohue, Shane; Renou-Wilson, Florence; O'Loughlin, Fiachra (The Science of the total environment, 2023)
Despite peatlands' important feedbacks on the climate and global biogeochemical cycles, predicting their dynamics involves many uncertainties and an overwhelming variety of available models. This paper reviews the most widely used process-based models for simulating peatlands' dynamics, i.e., the exchanges of energy and mass (water, carbon, and nitrogen). ‘Peatlands’ here refers to mires, fens, bogs, and peat swamps both intact and degraded. Using a systematic search (involving 4900 articles), 45 models were selected that appeared at least twice in the literature. The models were classified into four categories: terrestrial ecosystem models (biogeochemical and global dynamic vegetation models, n = 21), hydrological models (n = 14), land surface models (n = 7), and eco-hydrological models (n = 3), 18 of which featured “peatland-specific” modules. By analysing their corresponding publications (n = 231), we identified their proven applicability domains (hydrology and carbon cycles dominated) for different peatland types and climate zones (northern bogs and fens dominated). The studies range in scale from small plots to global, and from single events to millennia. Following a FOSS (Free Open-Source Software) and FAIR (Findable, Accessible, Interoperable, Reusable) assessment, the number of models was reduced to 12. Then, we conducted a technical review of the approaches and associated challenges, as well as the basic aspects of each model, e.g., spatiotemporal resolution, input/output data format and modularity. Our review streamlines the process of model selection and highlights: (i) standardization and coordination are required for both data exchange and model calibration/validation to facilitate intercomparison studies; and (ii) there are overlaps in the models' scopes and approaches, making it imperative to fully optimize the strengths of existing models rather than creating redundant ones. In this regard, we provide a futuristic outlook for a ‘peatland community modelling platform’ and suggest an international peatland modelling intercomparison project. [Display omitted] •An extensive systematic search identified many process-based models being used for peatland dynamics.•Only about a quarter of the models meet the FOSS and FAIR criteria for an open-source and active community.•It is essential to standardize model calibration/validation and data sharing.•No one-size-fits-all model exists, but the models overlap in scope and approach.•A peatland community modelling platform can optimally exploit the strengths of existing models.